Analysis of the effect of the current ratio, debt to equity ratio, and return on assets on stock returns of food and beverage companies on the Indonesian stock exchange for the period 2008-2010 - Aryo Hendrakusuma (Institute of Accounting Research and Novation (IARN), 2022)
Firm financial performance had large influence toward stock returns. The effect of those indicators could be positive or negative. Many investigations show that firm financial performance such as current ratio, debt to equity ratio, and return on assets have a positive or negative impact toward stock returns. The purpose of this research is to analyze the influence of firm financial performance such as the current ratio, debt to equity ratio, and return on assets toward stock returns on food and beverage on the Indonesia Stock Exchange in the period of 2008-2010. The election procedure of the sample is purposive sampling. The sample of this research consists of 17 food and beverage companies. Data analysis with multiple regression and hypothesis test used t test and F test at level of significance 5%. Examination of classic assumptions to eliminate disturbances of multicollinearity, heteroscedasticity, and autocorrelation which emerge at regression equation. Significance test indicated that common effect is the most appropriate method to analyze. The results of this research show that the current ratio and return on variable assets has a positive and significant influence toward stock returns. This result is expected to be made as a reference, either by company management and also by investors in determining investment strategy